Deciphering Reparative Processes in the Inflamed Dental Pulp - El karim, Ikhlas A.; Cooper, Paul R.; About, Imad; Tomson, Phillip L.; Lundy, Fionnuala T.; Duncan, Henry F. (Frontiers in Dental Medicine, 2021)
Research over several decades has increased our understanding of the nature of reparative and regenerative processes in the dental pulp, at both the cellular and molecular level. However, advances in scientific knowledge have not translated into novel clinical treatment strategies for caries-induced pulpitis. This narrative review explores the evidence regarding the ability of inflamed pulp tissue to heal and how this knowledge may be used therapeutically. A literature search and evidence analysis covering basic, translational and clinical pulp biology research was performed. The review focuses on (1) the regenerative and defence capabilities of the pulp during caries-induced inflammation; (2) the potential of novel biomaterials to harness the reparative and regenerative functions of the inflamed pulp; and (3) future perspectives and opportunities for conservative management of the inflamed pulp. Current conservative management strategies for pulpitis are limited by a combination of unreliable diagnostic tools and an outdated understanding of pulpal pathophysiological responses. This approach leads to the often unnecessary removal of the entire pulp. Consequently, there is a need for better diagnostic approaches and a focus on minimally-invasive treatments utilising biologically-based regenerative materials and technologies